Antibacterial effect of calcium hydroxide with or without chlorhexidine as intracanal dressing in primary teeth with apical periodontitis - Silva, Lea A.B.; Romualdo, Priscilla C.; Silva, Raquel A.B.; Souza-Gugelmin, Maria C.M.; Pazelli, Luciana C.; De Freitas, Aldevina C.; Faria, Gisele [UNESP]; Nelson-Filho, Paulo (My University, 2017)
Purpose: The purpose of this study was to evaluate in vivo the antibacterial effect of calcium hydroxide (CH) dressings, with or without chlorhexidine (CHX), on human primary teeth with apical periodontitis. Methods: Forty root canals in 40 children were selected. A first microbiological sample was obtained after coronal opening, and the teeth were randomly assigned to Group 1 (root canals filled with CH paste) and Group 2 (CH paste plus 1.0 percent CHX). After 30 days, the dressing was removed and the canals were allowed to remain empty for 72 hours. Subsequently, the second microbiological sample was collected. After performing microbiological tests, the data were subjected to statistical analysis to compare the two CH dressings regarding reducing the absolute levels of microorganisms and with respect to total microbial elimination. All analyses were performed with a significance level of five percent. Results: Both CH dressings provided a significant reduction in the number of microorganisms (anaerobic, aerobic, black-pigmented bacilli, streptococci and Streptococcus mutans) in a similar way (P>0.05). However, in terms of complete elimination of microbiota, CH paste alone exhibited greater efficacy (P<0.05). Conclusions: The addition of chlorhexidine did not provide additional antimicrobial benefits compared with pure calcium hydroxide paste as an intracanal dressing in primary teeth with apical periodontitis.
Keywords: CALCIUM HYDROXIDE; CHLORHEXIDINE; DRESSING; PRIMARY TEETH